Beauty attracts the eye but personality captures the heart … of digital transformation in crafts SMEs - Thore Sören Bischoff; Anita Thonipara (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2023)
Digital transformation determines the long-term viability of SMEs but poses particular challenges for crafts SMEs due to their lack of resources and their individualized products and services. We argue that the unique personality of a crafts owner is a missing link in the literature on the firm-level drivers of digitalization. Using the Big Five personality model, data of 554 crafts SMEs and quantitative methods, our results provide evidence that the personality traits of extraversion and openness are particularly beneficial for overall digitalization in crafts companies. Furthermore, we show that different personality traits are important at different maturity levels of digitalization and that the effect of personality on digitalization is to some extent mediated by the owner's local embeddedness.
Keywords: O31; O32; 330; Digital transformation; Crafts; Personality; Big Five; SMEs